DISFEMISME PADA KOLOM KOMENTAR AKUN INSTAGRAM @rahmawatikekeyiputricantikka23 - Kusumastuti, Widya Ayu; Aziza, Anisa Nur; Wardani, Amalia Kusuma; Hidayati, Ika Nurul (Hasta Wiyata, 2021)
Social media becomes a space to express feelings and opinions freely. However, freedom of speech is now abused by internet citizens to freely express words that mean rude, blasphemous, insulting, or in language science called disfemism. This research aims to describe the form and function of disfemism in the comment column of kekeyi public figure's Instagram @rahmawatikekeyiputricantikka23. The research method uses a descriptive qualitative method. The research data are words, phrases, and sentences containing disfemism in the comments column of the Instagram @rahmawatikekeyiputricantikka23 in July 2020. The data collection method uses the simak method with a recording techniqueâ€”data collection techniques with documentation techniques. Data analysis uses the agih method with basic natural elements, substitution or substitution techniques, and Â removal techniques. Based on the results of this study found 279 data on disfemism. The found forms of disfemism are words, phrases, and phrases. The word disfemism form amounts to 90 data, the form of phrase disfemism amounts to 100 data, and the expression disfemism form amounts to 89 data. There are seven functions of disfemism found in this study, among them: (a) as an intermediary to express taboo or indecent things, (b) as a sign of dislike, hate, and disrespect, (c) as an intermediary to express anger or aggravation, (d) as a negative depiction of something, (e) as a means of insulting and mocking, (f) as a means of criticizing, and (g) as a means to exaggerate something and scold.